Lost in the game : a book about basketball - Beller, Thomas (Duke University Press, 2022)
"For players, coaches, writers, and fans, basketball is a science and an art, a religious sacrament, a source of entertainment, and a way of interacting with the world. In Lost in the Game Thomas Beller entwines these threads with his lifetime experience as a player and journalist, roaming NBA locker rooms and city parks alike as a basketball flâneur in search of the meaning of the modern game. He captures the magnificence and mastery of today's most accomplished NBA players while paying homage to the devotion of the countless congregants in the global church of pickup basketball. He shares his own stories on the court, meditating on basketball's role in city life and its impact on the athlete's psyche as he moves from youth to middle age. Part journalistic account, part memoir of a slightly talented player whose main gift is being tall, Lost in the Game charts the game's inexorable gravitational hold on those who love it."--